Buck [videorecording (DVD)] - Meehl, Cindy; Redford, Robert; Brannaman, Buck (IFC Films, 2011)
A richly textured and visually stunning film, follows Buck Brannaman from his abusive childhood to his phenomenally successful approach to horses. A real-life 'horse-whisperer', he eschews the violence of his upbringing and teaches people to communicate with their horses through leadership and sensitivity, not punishment. Buck possesses near magical abilities as he dramatically transforms horses, and people, with his understanding, compassion and respect.